Clutches of the Cat-eye snakes genus Leptodeira spp. (SERPENTES: Dipsadidae), with a bibliographic review and new reports for Panama - Fuentes, Rogemif; Barría, Erick; Quiroz-Espinoza, Michelle; Zambrano, Eduardo; Cleghorn, John; Añino, Yostin (Revista Científica Vida Natural, 2024)
The reproduction of Neotropical snakes, such as those of the genus Leptodeira, varies widely influenced by climatic factors, with species ranging from strictly seasonal to continuous reproductive patterns. Recent research reveals significant variability in reproductive cycles, determined by local environmental conditions such as temperature and precipitation. Nesting behaviors remain poorly understood, and snakes use diverse environments, from natural shelters to communal nests of other species. Within the family Dipsadidae, species such as L. maculata and L. punctata demonstrate correlations between female body size (SVL) and clutch size, reflecting adaptive strategies to maximize reproductive success in diverse ecological contexts. Field work in Panama provided new insights, documenting egg-laying and gravid individuals of species such as L. rhombifera and L. ornata, highlighting further research to elucidate the reproductive dynamics and ecological adaptations particular to each. species. Analytical approaches including Pearson and Spearman correlations and cluster analysis reveal distinct patterns in clutch size relative to female size, underscoring species adaptations and variability within the genus.